The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017 IEEE International Conference on Robotics and Automation (ICRA) 2017
DOI: 10.1109/icra.2017.7989183
|View full text |Cite
|
Sign up to set email alerts
|

Supervisory teleoperation with online learning and optimal control

Abstract: Abstract-We present a general approach for online learning and optimal control of manipulation tasks in a supervisory teleoperation context, targeted to underwater remotely operated vehicles (ROVs). We use an online Bayesian nonparametric learning algorithm to build models of manipulation motions as task-parametrized hidden semi-Markov models (TP-HSMM) that capture the spatiotemporal characteristics of demonstrated motions in a probabilistic representation. Motions are then executed autonomously using an optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Therefore, the generalization of the demonstrated trajectories to new situations is not concerned. Recent follow-up work [Havoutis and Calinon, 2017] addressed the online learning and the adaptation of the skill to new contexts by combining an optimal control approach and TP-GMM in [Calinon, 2015]. used ProMPs for incremental imitation with generalization to different contexts.…”
Section: Incremental Trajectory Learningmentioning
confidence: 99%
“…Therefore, the generalization of the demonstrated trajectories to new situations is not concerned. Recent follow-up work [Havoutis and Calinon, 2017] addressed the online learning and the adaptation of the skill to new contexts by combining an optimal control approach and TP-GMM in [Calinon, 2015]. used ProMPs for incremental imitation with generalization to different contexts.…”
Section: Incremental Trajectory Learningmentioning
confidence: 99%
“…The red dotted line is the motion predicted by the model from the current robot state. The gray square in the robot space represents what the robot end-effector state would be with a direct teleoperation behavior, which would only poorly match the current situation in the robot space (Color figure online) et al (2016) and Havoutis and Calinon (2017), we showed how such a model can be learned in an online manner, and be used in a teleoperation scenario with failing communication, to semi-autonomously perform an ROV task (hot-stabbing) using an MPC formulation for motion generation.…”
Section: Related Workmentioning
confidence: 99%
“…In (Farooq et al, 2016), the authors presented a state convergence-based control method with a Takagi-Sugeno (TS) fuzzy model for nonlinear teleoperation system. Havoutis et al (Havoutis et al, 2017) developed an integrated method involving optimal control and online learning to accomplish a manipulation task for underwater remotely operated vehicles during supervisory teleoperation. Additionally, Daniel et al proposed a user-controlled variable impedance method with implicit haptic feedback for unstructured environments (Walker et al , 2010).…”
Section: Introductionmentioning
confidence: 99%